Cost-efficient data aggregation point placement for advanced metering infrastructure - Aalamifar, Fariba; Shirazi, Ghasem Naddafzadeh; Noori, Moslem; Lampe, Lutz (2014 IEEE International Conference on Smart Grid Communications (SmartGridComm), 2014)
This paper investigates the problem of placement of data aggregation points (DAPs) in advanced metering infrastructures (AMIs). The specific constraints are that DAPs are to be located on utility poles and that communication is done over wireless links. While the resulting optimization problem is an integer program, we propose to adapt the K-means algorithm to obtain an efficient and less-complex method to solve the DAP placement problem. Simulations of the developed optimization method illustrate the effects of smart-meter density and communication range on the selection of DAP locations.